Utilizing Virtual Reality (VR) and Augmented Reality (AR) Technologies in EFL Classrooms: A Novel Approach to Improve Vocabulary Learning and Retention - Jwai،ed, Alanoud Mustafa; Masri, Amaal Al; Hijazi, Dima; Smadi, Mona (Journal of Ecohumanism, 2024)
This study investigates the potential for EFL courses to benefit from VR and AR technologies to enhance vocabulary learning and retention. The study included 220 English language and literature students from English departments at colleges, including Al Balqa Applied University and Al Yarmouk University in Jordan. The implications and data generated from this study aim to provide insights into how new immersive technologies can be applied, compared to traditional methods, in an educational context to enhance vocabulary acquisition. Pre- and post-tests measured vocabulary acquisition, and the delayed post-test was conducted weeks after the study was completed to measure the acquisition and retention of vocabulary. The study demonstrates significant differences in vocabulary acquisition following the intervention using VR and AR technologies compared to traditional learning methods. The average scores before the pretest were similar in all groups, with VR at 45.2, AR at 46.0, and control at 44.8. The results of the post-test, however, had average scores for VR at 78.5, AR at 75.3, and control at 58.4. The direction of the measures indicated significant improvements in vocabulary acquisition among the students in the English departments at the universities who used VR and AR technologies. The study is prospective; VR and AR technologies significantly improve vocabulary acquisition in EFL learning environments.